FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR (Studi Pada KAP Pekanbaru, Padang, Medan) - Gantri Andini; Kamaliah '; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The Purpose of this study was to examine the effect of audit structure, organizational commitment, role conflict,and the technology information on the performance of auditors. The location study this object is a KAP Pekanbaru, Padang and Medan. While the timing of this study in a Juni 2016. The sample use were as many as 93 auditors respondens. This research is using purposive sampling method. Data collection method used in this research is to use the instrument in the form of a questionnaire which was given the auditor of the KAP Pekanbaru, Padang and Medan. The analyzing method is Double Regression Methods using SPSS (Statistical Product and Service Solution) version 20. Based on the data collected and testing has been done on the problem by using regression analysis method, it can be concluded: (1) Audit Structure has 0,012 significant influence on the performance of auditors, (2) Organizational Commitment has 0,029 significant influence on the performance of auditors, (3) Role Conflict has 0,000 significant influence on the performance of auditors, (4) the technology information has 0,002 significant influence on the performance auditor.All of the independent variables jointly influence dependent variables as much 64%, while 36% is influenced by other unclear variable.Keywords : Audit, Organizational, Commitment, Culture and Performance